1989
DOI: 10.1073/pnas.86.7.2316
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class I-restricted activation of cloned T cells by a soluble protein in the absence of accessory cells.

Abstract: A T-cell clone, 10BK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The Th1 cell clone BK-OVA-1R [7], which constitutively expresses IL-2R in low density, and the T-cell hybridoma 3DO-54.8 [17], both specific for OVA in combination with A b A k and I-A d , respectively, were established as described. BK-BI-2.6.O4.1 (BI/O4.1), an Ia-positive T-cell clone of (B106B10.BR) F1 origin, is able to present various protein Ag to Ag-specific CD4 + T cells [6]. A20/2 J is a mouse B-cell lymphoma derived from a BALB/c tumour [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Th1 cell clone BK-OVA-1R [7], which constitutively expresses IL-2R in low density, and the T-cell hybridoma 3DO-54.8 [17], both specific for OVA in combination with A b A k and I-A d , respectively, were established as described. BK-BI-2.6.O4.1 (BI/O4.1), an Ia-positive T-cell clone of (B106B10.BR) F1 origin, is able to present various protein Ag to Ag-specific CD4 + T cells [6]. A20/2 J is a mouse B-cell lymphoma derived from a BALB/c tumour [18].…”
Section: Methodsmentioning
confidence: 99%
“…Various cell types expressing class II molecules can act as APC, such as dendritic cells, B cells, lymphokine-activated macrophages and I-A transfected L-cells. We have reported on the Ag presentation capacity of the murine T-cell clone BK-BI-2.6.O4.1 (BI/O4.1) that constitutively synthesizes and expresses class II molecules [5,6]. The responding protein Ag-specific T clone cells were induced to produce lymphokines including IL-2.…”
Section: Introductionmentioning
confidence: 99%
“…A CD8 T and major histocompatibility complex (MHC) class I (HLAlymphocyte clone (TLC) can present cognate peptides to itself B27) -restricted CD8 ab TCR / cytotoxic T cells (CTL) [7] in the absence of other APC, and this mechanism of antigen with specificity for bacterial antigens are involved in the pathopresentation can induce proliferation [12] or death [13] of the genesis and maintenance of ReA. In the experiments reported, CTL.…”
Section: Rea Recognized and Efficiently Lysed Autologous And Allogenementioning
confidence: 99%
“…In the experiments reported, CTL. A CD8 TLC, 10BK.1, recognizes an exogenous soluble B cell lines and monocytes were used as professional antigenovalbumin-derived peptide together with MHC class I (H-2K b ) presenting cells (APC) in both proliferation and cytotoxicity molecules [12]. This clone has the capacity for self-presentation assays.…”
Section: Rea Recognized and Efficiently Lysed Autologous And Allogenementioning
confidence: 99%
“…The consequences of such an inter-CTL antigen presentation can be lysis of the presenting CTL [14] as well as the stimulation of CTL to proliferation [3]. In previous studies we have shown that CTL clone 10BK.1 with specificity for the ovalbumin (OVA) peptide OVA 257 -264 proliferates after incubation with the soluble cognate peptide in the absence of added syngeneic APC, thus suggesting antigen self-presentation by the T cells [3,25]. In addition to the proliferative response, we observed lysis of syngeneic as well as allogeneic target cells after antigen self-presentation.…”
Section: Introductionmentioning
confidence: 99%